2020
DOI: 10.1016/j.celrep.2020.01.097
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Asymmetric and Symmetric Divisions of Muscle Stem Cells In Vivo and on Artificial Niches

Abstract: Highlights d Muscle stem cells divide symmetrically and asymmetrically in vivo d Muscle stem cells can switch from asymmetric to symmetric cell division ex vivo d Histone H3-SNAP reporters allow turnover measurements in vivo d H3.1 and H3.3 are symmetrically distributed during muscle stem cells divisions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 76 publications
2
32
1
Order By: Relevance
“…During induced asymmetric divisions of these embryonic stem cells, parental histone H3 and H4 was selectively segregated to the daughter stem cells, while newly synthesized histone H3 and H4 was enriched toward the epiblast stem daughter cell (Ma et al 2020). This pattern of histone (Evano et al 2020) distribution was similar to that found in the Drosophila male germline stem cells under asymmetric cell division. The asymmetric H3 and H4 inheritance mode may serve as a more general mechanism during the asymmetric cell division of stem cell in Drosophila and mouse embryonic stem cell, and in germline stem cell and embryonic stem cell.…”
Section: Dual-color Switching Systems and Pulse-chase Labeling Approasupporting
confidence: 72%
See 2 more Smart Citations
“…During induced asymmetric divisions of these embryonic stem cells, parental histone H3 and H4 was selectively segregated to the daughter stem cells, while newly synthesized histone H3 and H4 was enriched toward the epiblast stem daughter cell (Ma et al 2020). This pattern of histone (Evano et al 2020) distribution was similar to that found in the Drosophila male germline stem cells under asymmetric cell division. The asymmetric H3 and H4 inheritance mode may serve as a more general mechanism during the asymmetric cell division of stem cell in Drosophila and mouse embryonic stem cell, and in germline stem cell and embryonic stem cell.…”
Section: Dual-color Switching Systems and Pulse-chase Labeling Approasupporting
confidence: 72%
“…The finding that MCM2 and Dpb3/Dpb4, both classical DNA replication machinery components, are involved in the transfer and allocation of parental histones has broadened our understanding of this important cellular process and its role in epigenetic inheritance. Different parental histone allocation patterns have been reported in Drosophila and mouse embryonic stem cells compared with mouse muscle stem cells, using dual-color switching methods and SNAP tag (Evano et al 2020;Ma et al 2020;Tran et al 2012;Wooten et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next performed FACS analysis to determine whether the tdTOM + mononucleated fraction could be isolated following tissue injury. As expected, only a few tdTOM + cells were detected at 3 days post-injury, when myogenic cells are known to be maximally proliferating [23,24,48] ( Figure 3B). tdTOM + cells were most abundant at 5 and 10 days post injury, corresponding to the differentiation shift of the transiently amplifying myoblast population.…”
supporting
confidence: 79%
“…High-resolution IVM imaging through the PDMS window revealed the movement and division of GFP+ cells at 3 days post-injury ( Fig. 3C, Movie S5), a time point at which muscle stem cells are maximally proliferating (29,31). Importantly, highresolution images could be acquired through PDMS windows with no observable decline in image quality for at least 18 days after injury ( Fig.…”
Section: Ivm Of Muscle Regeneration Through Pdms Imaging Windowsmentioning
confidence: 92%